PENERAPAN ELECTRONIC COMMERCE SEBAGAI UPAYA MENINGKATKAN PENJUALAN PRODUK - Irawan, Johan Sugianto (Kajian Ilmiah Mahasiswa Manajemen, 2012)
This era of globalization, information and rapid way of trading, e-commerce is one of the most popular tools to gain a competitive advantage over other organizations for the company. Effective and efficient in all it is a necessity in the business world, with e-commerce everything can be completed in a matter of minutes to get the information, communications, promotions, increase sales, and sales transactions to consumers wherever the consumer is. E-marketing, a new term in the world of marketing is done in cyberspace. Forms of marketing is launched with the help of some media liaison. Keywords: E-